Structural Properties of Lead Oxide-Doped Zinc Tellurite Glasses - Hiwa L. Hamad; Saman Q. Mawlud (Zanco Journal of Pure and Applied Sciences, 2024)
The melt quenching technique was used to create a ternary (90-x) TeO2 - xPbO -10ZnO glass system (x = 0, 10, 20, 25, 30, 35, and 40 mol%). The X-ray diffraction (XRD) technique is used for improving the amorphous nature of the glass samples. In addition, to examine the structural characteristics of the glass samples, scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy are used. Raman spectroscopy was used to evaluate the impact of PbO on the glass structure. A strong frequency peak at 729.63-774.69 cm-1 was detected in the Raman spectra, indicating that the TeO4 and TeO3/TeO3+1 structural units make up the majority of the glass network. The TeO3/TeO3+1 structural unit contain non-bonding oxygen molecules that are stretched in the Pb-O, Zn-O, Te-O, and Te-O-Te bridging configurations, vibrations, and Raman spectra.